Correlation between temporomandibular disorders, occlusal factors and oral parafunction in undergraduate students - Fabiane Maria Ferreira; Paulo Cézar Simamoto-Júnior; Veridiana Resende Novais; Marcelo Tavares; Alfredo Julio Fernandes-Neto (Universidade Estadual de Campinas, 2010)
Aim: To investigate the prevalence of temporomandibular disorders (TMD) in undergraduate students and to correlate its prevalence with occlusal factors and parafunctional habits. Methods: 201 undergraduate students were evaluated. The Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) was filled out at the beginning of the study, followed by occlusal analysis based on morphological and functional alterations. The identification of tooth grinding and clenching was carried out by self-reports. Statistical analysis was based on chisquare and multivariate logistic regression analyses. p-value for all statistical analysis was set at 5%. Results: According to RDC/TMD, 18.4% of subjects experienced myofascial pain (GMPD), and 12.4% had joint disorder with disc displacement (G-DD). Tooth clenching was statistically associated with TMD (p=0.000). In the occlusal factors, overjet showed statistically significant correlation only with myofascial pain. No association between functional alteration and TMD was found. No statistically significant correlation was found between G-DD and occlusal alterations or parafunctional habits. Conclusions: Overjet and tooth clenching were correlated with G-MPD. Occlusal alterations or parafunctional habits did not show correlation with G-DD.